Effects of intake charge temperature and relative air-fuel ratio on the deterministic characteristics of cyclic combustion dynamics of a HCCI engine. (May 2023) - Singh, Ajay; Maurya, Rakesh Kumar
Homogenous charge compression ignition (HCCI) combustion can significantly reduce automotive pollution and increase the thermal efficiency of the engine. However, combustion phasing control is a major challenge in HCCI engines due to severe cyclic combustion variations. This study investigates the cyclic combustion dynamics of the HCCI engine using nonlinear dynamic methods such as return maps, recurrence plots (RPs), and recurrence quantitative analysis (RQA). Combustion stability and cyclic variations of HCCI combustion parameters were investigated on a modified four-stroke diesel engine. The experiments were conducted by varying relative air-fuel ratios (λ ) and intake air temperatures (T i ) at two engine speeds. In-cylinder pressure data of 2000 consecutive engine combustion cycles is logged for each test condition. In this study, deterministic characteristics of combustion phasing (CA50 ) and crank angle position of maximum cylinder pressure (θ P max ) are investigated and compared by employing nonlinear dynamical methods. Return maps revealed thatθ P max is having distinct and more frequently observed deterministic characteristics in comparison to CA50 . Patterns in RPs showed a more persistent and sudden change in the combustion dynamics at higher engine speeds. Recurrence plot-based analysis found the existence of deterministic features in the combustion dynamics irrespective of the operating conditions. It was found using RQA parameters that the deterministic nature becomes stronger with a decrease inT i and any deviation in intermediate values ofλ . Additionally, RQA measures advocate that CA50 has more deterministic characteristics at higher engine speed whileθ P max at lower engine speed. Strong coupling and synchronization betweenθ P max and CA50 is indicated by cross-recurrence plots and CPR index when engine operated with a comparatively richer mixture.